Analisis Pelayanan Check-In Counter Maskapai Batik Air Terhadap Kepuasan Penumpang di Bandar Udara Komodo Labuan Bajo - Ismi Zakiyah; Gallis Nawang Ginusti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Batik Air's check-in counter service has not been maximized. Like when checking in the old officer in handling passengers. because there is only 1 check-in counter which results in a relatively long queue buildup. The purpose of this study is to (1) find out how is the check-in counter service of for Batik Air passengers at Komodo Airport (2) Labuan Bajo and their level of satisfaction on the service. This study uses a qualitative approach. The results of this study, for the Check-in Counter service is good and is in accordance with the provisions of PM No. 49 of 2012 and Doc. No: TND/SOP-01. From these results, the average passenger who uses Batik Air Airlines is satisfied with the services provided by the Batik Air Airlines check-in counter